Source tracking Mycobacterium ulcerans infections in the Ashanti region, Ghana. - Charles A Narh; Lydia Mosi; Charles Quaye; Christelle Dassi; Daniele O Konan; Samuel C K Tay; Dziedzom K de Souza; Daniel A Boakye; Bassirou Bonfoh (Public Library of Science (PLoS), 2015)
Although several studies have associated Mycobacterium ulcerans (MU) infection, Buruli ulcer (BU), with slow moving water bodies, there is still no definite mode of transmission. Ecological and transmission studies suggest Variable Number Tandem Repeat (VNTR) typing as a useful tool to differentiate MU strains from other Mycolactone Producing Mycobacteria (MPM). Deciphering the genetic relatedness of clinical and environmental isolates is seminal to determining reservoirs, vectors and transmission routes. In this study, we attempted to source-track MU infections to specific water bodies by matching VNTR profiles of MU in human samples to those in the environment. Environmental samples were collected from 10 water bodies in four BU endemic communities in the Ashanti region, Ghana. Four VNTR loci in MU Agy99 genome, were used to genotype environmental MU ecovars, and those from 14 confirmed BU patients within the same study area. Length polymorphism was confirmed with sequencing. MU was present in the 3 different types of water bodies, but significantly higher in biofilm samples. Four MU genotypes, designated W, X, Y and Z, were typed in both human and environmental samples. Other reported genotypes were only found in water bodies. Animal trapping identified 1 mouse with lesion characteristic of BU, which was confirmed as MU infection. Our findings suggest that patients may have been infected from community associated water bodies. Further, we present evidence that small mammals within endemic communities could be susceptible to MU infections. M. ulcerans transmission could involve several routes where humans have contact with risk environments, which may be further compounded by water bodies acting as vehicles for disseminating strains.